Strategi Komunikasi Pemasaran Sosial Kampung Bebas Narkoba Pada Badan Narkotika Nasional - Tjangkung Josephien Vivick (KOM & REALITAS SOSIAL, 2010)
This research focused on social marketing communications strategic of Kampung Bebas Narkoba (Free Drug Village) with case study approach that focused reveal program design, communication patterns, the process of implementation, quality of communications, and program development conducted the National Narcotics Board. This research found that social marketing perspective can be used as a tool for community development evaluation. In particular, the most favorable strategy to sustain community empowerment is interactive communications with involving and accommodating the public needs.